Physiological maturity in maize (Zea mays L.) seeds through morphological markers and moisture content - Estrada-Urbina, Juan (2023)
Introduction. Physiological maturity is the accumulation of the maximum dry matter content, the milk line and the black layer affect the corn seed, as morphological factors of the degree of maturation. The milk line is related to the solidification of starch, and the black layer with the cessation of the translocation of soluble substances from the plant to the grain. The moisture content is related to the physiological maturity and the harvest opportunity associated with the maximum quality of the product. Objective.  Determine seeds physiological maturity, through morphological markers and moisture content, and its physiological quality relationship. Materials and methods. The study was carried out at Colegio de Postgraduados, Campus Montecillo during the months of September-October, 2021. By weekly sampling cobs of experimental cv. (Amarillo × V-54A) F6 genotype, seeds from the apex were taken, middle section and basis. In function by its moisture content, the milk line, black layer, and the relationship of these factor with physiological quality (germination and vigor- accelerated aging and cold tests) were determined. Results. Moisture content was below than referred in literature (35 %), also, physiological maturity was defined visually by milk line and black layer; on the other hand, as sampling were done, there was an increase in seed germination with the less moisture content; what vigor refers, a better response was detected by accelerated aging test. Conclusions. As the moisture content decreased, germination increased. The morphological markers allowed to determine the time in which the maize seed reached the physiological maturity and with it, the maximum quality.